IMPLEMENTASI STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PADA SISWA CALISTUNG DI SANGGAR BIMBINGAN SUNGAI MULIA 5 GOMBAK KUALA LUMPUR - Alviyatus Sholihah; Iwan Kuswandi; Ike Yuli Mestika Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In improving literacy and numeracy you must also have motivation. Motivation here has an important role in teaching and learning activities both from the teacher and student side. Motivation also has important components, the components in motivation are needs, encouragement and goals. The aim of this research is to increase the motivation of Calistung students at the Sungai Mulia 5 Gombak Guidance Studio in Kuala Lumpur by implementing the strategies provided by the teacher in their learning to grow the abilities of Calistung students at the Sungai Mulia 5 Gombak Guidance Studio. The results of this research, the process of implementing the teacher's strategy here really helps students at the Sungai Mulia 5 Gombak Guidance Studio to become more enthusiastic about their desires to know, students make more effort to become knowledgeable, when carrying out their assignments they try to do their assignments both correctly and incorrectly. So that student motivation increases, not just participating in learning by playing.